Architects' perception of resilient design for building in Malaysia / Nur Amalina Fuad, Mohd Najib Mohd Salleh and Azhar Ghazali - Fuad, Nur Amalina; Mohd Salleh, Mohd Najib; Ghazali, Azhar (2022)
The 'resilience' approach has become increasingly prominent in architecture in recent years. Their significant effects on national and global economies have prompted action to improve building resilience. These challenges are overcome only by making buildings better, innovative, and resilient. Despite its current influence, the literature lacks studies that comprehensively understand architect perception related to resilient design in a built environment. In this context, this study examines the perception of Malaysian architects on the application of resilient design strategies to buildings in Malaysia. The focus on architects' disaster resilience knowledge originates from the inadequacy of conventional building design in dealing with natural disasters. This study employed a quantitative method using structured questionnaires to identify the respondents' views. The selected respondents are architects due to their direct involvement in conceptualizing, planning, designing, and constructing a built environment project. The research first identified the risks facing buildings in Malaysia and built resilience indicators through a literature review of available resilient strategies from journals, articles, and thesis to interpret the key resilience strategies used as variables measurement in this study. The findings revealed that there is a positive perception by the architects regarding the application of resilient design in Malaysia. Identifying the perception of architects within the context of resilient design can lead to a basis for developing a practical scheme for the improvement of building resiliency in Malaysia.